Use of Electrocautery for Coagulation and Wound Complications in Caesarean Sections - Cristiane M. Moreira; Eliana Amaral (The Scientific World Journal)
Objective. To evaluate the safety of electrocautery for coagulation during Caesarean sections. Study Design. A randomized, controlled, clinical pilot study was performed at a university maternity hospital. After admission for delivery and decision to perform a C-section, volunteers were randomized to either the intervention group (use of electrocautery for coagulation) or nonintervention group. The women were examined at the time of postpartum discharge (day 3), at days 7 to 10, and again at days 30 to 40 for signs of infection, hematoma, seroma, or dehiscence. Data were analyzed using an intention-to-treat analysis, and risk ratios were calculated. Results. No significant differences were found between the two groups. Only 2.8% of patients in the intervention group developed surgical wound complications during hospitalization. However, 7 to 10 days following discharge, these rates reached 23.0% and 15.4% in the intervention and nonintervention groups, respectively (RR = 1.50, 95% CI = 0.84–2.60). Conclusion. Further studies should confirm whether the use of electrocautery for coagulation does not increase the risk of surgical wound complications in patients undergoing Caesarean sections.